2021
DOI: 10.1002/dev.22174
|View full text |Cite
|
Sign up to set email alerts
|

Paternal adverse childhood experiences: Associations with infant DNA methylation

Abstract: Adverse childhood experiences (ACEs), or cumulative childhood stress exposures, such as abuse, neglect, and household dysfunction, predict later health problems in both the exposed individuals and their offspring. One potential explanation suggests exposure to early adversity predicts epigenetic modification, especially DNA methylation (DNAm), linked to later health. Stress experienced preconception by mothers may associate with DNAm in the next generation. We hypothesized that fathers’ exposure to ACEs also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 192 publications
(293 reference statements)
1
24
0
Order By: Relevance
“…It was similarly reported that the impact of exposure to a stressor over 6 weeks prior to breeding led to paternal epigenetic effects [ 133 ]. Consistent with studies in animals, the paternal transmission of epigenetic changes stemming from ACEs in humans was linked to attention problems apparent in their offspring [ 134 ]. The early-life stressful experiences of a male parent were similarly associated with altered brain development in neonates, even after controlling for multiple maternal factors [ 135 ].…”
Section: Epigenetic Changes Related To Stressful Eventsmentioning
confidence: 54%
“…It was similarly reported that the impact of exposure to a stressor over 6 weeks prior to breeding led to paternal epigenetic effects [ 133 ]. Consistent with studies in animals, the paternal transmission of epigenetic changes stemming from ACEs in humans was linked to attention problems apparent in their offspring [ 134 ]. The early-life stressful experiences of a male parent were similarly associated with altered brain development in neonates, even after controlling for multiple maternal factors [ 135 ].…”
Section: Epigenetic Changes Related To Stressful Eventsmentioning
confidence: 54%
“…Numerous substudies, employing portions of the APrON sample, have utilized the originally collected biosamples in related research; for example, the Neurotoxicant Study (n=546) that examined maternal exposure to endocrine hormone disrupting chemicals (i.e., bisphenol A and phthalates) on child outcomes8–13 and the Parenting Research on Mental Illness, Stress and Epi/genetics (PROMISE; n=276) Study of gene-by-environment interactions 14–18 19–2619–27 (n=276) collected additional data such as maternal and infant saliva for cortisol assessment, infant heart rate variability, and parent-infant interactions via videotaped observations.…”
Section: What Has the Apron Study Measured?mentioning
confidence: 99%
“…For example, the identification of BRCA gene variants for breast cancer or MSH2, MSH6 and MLH1 for colon and extracolonic cancers have resulted in screening programs and therapies that have changed the trajectory and outcomes of these diseases. Genomics provides insight into how early life experiences affect health and disease over one's lifespan and across generations (Letourneau et al 2020(Letourneau et al , 2021Merrill et al 2021). Genomics is creating opportunities for health system transformation, including new or revised care pathways and patient engagement in health promotion and disease prevention.…”
Section: Introductionmentioning
confidence: 99%